2016
DOI: 10.1074/jbc.m116.719823
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin 6 Contributes to Cl− Secretion in Accessory Cholera Enterotoxin (Ace)-stimulated Diarrhea

Abstract: Edited by F. Anne StephensonAccessory cholera enterotoxin (Ace) of Vibrio cholerae has been shown to contribute to diarrhea. However, the signaling mechanism and specific type of Cl ؊ channel activated by Ace are still unknown. We have shown here that the recombinant Ace protein induced I Cl of apical plasma membrane, which was inhibited by classical CaCC blockers. Surprisingly, an Ace-elicited rise of current was neither affected by ANO1 (TMEM16A)-specific inhibitor T16A (inh) -AO1(TAO1) nor by the cystic fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Recent evidence shows that TMEM16 proteins are also regulated by PI(4,5)P2. For example, the TMEM16F phospholipid scramblase is regulated by PI(4,5)P2 in intestinal epithelia stimulated with the accessory cholera enterotoxin (Aoun et al, 2016). This might be because TMEM16F and also TMEM16C, -D, -G, and -J are phospholipid scramblases that transport membrane phospholipids between leaflets of the membrane bilayer (Suzuki et al, 2010; Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence shows that TMEM16 proteins are also regulated by PI(4,5)P2. For example, the TMEM16F phospholipid scramblase is regulated by PI(4,5)P2 in intestinal epithelia stimulated with the accessory cholera enterotoxin (Aoun et al, 2016). This might be because TMEM16F and also TMEM16C, -D, -G, and -J are phospholipid scramblases that transport membrane phospholipids between leaflets of the membrane bilayer (Suzuki et al, 2010; Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cl − secretion to induce diarrhea (Aoun et al, 2016). ANO6 and PIP 2 act as additional mechanisms of secretory diarrhea.…”
Section: Accessory Cholera Enterotoxin (Ace) and Zonula Occludens Toxmentioning
confidence: 99%
“…The role of ANOs in diarrhea is well-investigated in NSP-4 of rotavirus. It was found that phosphatidylinositol 4,5-bisphosphate (PIP 2 ) influences the ANO6 function by Ace stimulation in intestinal epithelium for Cl − secretion to induce diarrhea (Aoun et al, 2016 ). ANO6 and PIP 2 act as additional mechanisms of secretory diarrhea.…”
Section: Major Toxins Produced By V Cholerae and mentioning
confidence: 99%
“…Inhibiting intestinal sodium absorption through inhibitors of the Na + transporter NHE3, such as SAR218034, results in an increase in fecal sodium excretion and reduction in systolic blood pressure in spontaneously hypertensive rats [14]. In addition to the sodium channels, there are several types of chlorine channels present in enterocytes, such as Ca 2+ -activated Cl - channel (CaCC) and cystic fibrosis transmembrane conductance regulator (CFTR), which are expressed on the apical or luminal membrane to mediate Cl - secretion [15-17]. It’s reported dietary genistein could regulate basal diabetic jejunum Cl - secretion in ob/ob female mice by reduce CFTR expression [18].…”
Section: Introductionmentioning
confidence: 99%